2007
DOI: 10.4161/cam.1.2.4332
|View full text |Cite
|
Sign up to set email alerts
|

Hela l-CaD Is Implicated in the Migration of Endothelial Cells/Endothelial Progenitor Cells in Human Neoplasms

Abstract: Caldesmon (CaD) is a major actin-binding protein distributed in a variety of cell types. No functional differences among the isoforms in in vitro studies were found so far. In a previous study we found that the low molecular caldesmon isoform (Hela l-CaD) is expressed in endothelial cells (ECs)/endothelial progenitor cells (EPCs) in tumor vasculature of various human tumors. Activation of cell motility is necessary for the navigation of the tip ECs during angiogenesis, and migration of EPCs from the bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…S2). Disassembly of vinculin-and talin-containing focal adhesions was observed in HeLa-l-CaD-positive endothelial cells (Zheng et al, 2007). Overexpression of l-CaD promotes cell movement, but inhibits cell contractility with a decrease in focal adhesions (Helfman et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…S2). Disassembly of vinculin-and talin-containing focal adhesions was observed in HeLa-l-CaD-positive endothelial cells (Zheng et al, 2007). Overexpression of l-CaD promotes cell movement, but inhibits cell contractility with a decrease in focal adhesions (Helfman et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, CaD expression induced by p53 suppresses Src-kinase-dependent podosome formation, which inhibits fibroblast and rat aortic SMC migration (Mukhopadhyay et al, 2009). By contrast, HeLa-l-CaD expression in endothelial cells and endothelial progenitor cells in the vasculature of various human tumors promotes cell migration for vasculogenesis and angiogenesis during tumor development (Zheng et al, 2004;Zheng et al, 2007). Of note, we observed that endogenous CaD in C2C12 myoblasts localized to the membrane ruffles, suggesting that CaD is involved in cell migration in C2C12 myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…CaD is an inhibitor of cell motility, and manipulation of CaD expression affects migration of several cell types (Mirzapoiazova et al, 2005;Yokouchi et al, 2006;Zheng et al, 2007). For example, increased CaD expression in human lung carcinoma A549 cells enhances stress fiber formation and reduces cell motility, whereas CaD depletion increases motility (Mayanagi et al, 2008).…”
Section: Phosphorylation Of Caldesmon By Pkgi Disrupts Its Interactiomentioning
confidence: 99%
“…Immunolabeling of the EPCs was done by IF staining on the specimens from the glioma patients. The staining procedure was as before (Zheng et al, 2007a, b, c). Following IF staining FISH was performed on cells in interphase with the use of Dual color Vysis®LSI® DNA probes (Abbott Laboratories, Abbott Park, IL) for EGFR/CEP7 and PTEN (10q23)/CEP10.…”
Section: Methodsmentioning
confidence: 99%